PERAN CSR, INTENSITAS MODAL, DAN INTENSITAS PERSEDIAAN DALAM MENJELASKAN AGRESIVITAS PAJAK: EVIDENCE DARI PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE - Sabila, Risti Yana; Melzatia, Shinta (Jurnal Ekonomi dan Bisnis (EK&BI), 2025)
This research aims to examine the influence of Corporate Social Responsibility, Capital Intensity, and Inventory Intensity on Tax Aggressiveness. Tax aggressiveness is an aggressive corporate action in responding to tax obligations to the government so that the amount of tax paid to the state is less. The population used is the property and real estate subsector companies listed on the Indonesia Stock Exchange for the 2019-2023 period totaling 70 companies. Sampling using purposive sampling method and the companies selected as samples were 22 companies. The data used in this study are secondary data obtained from financial reports and annual reports through the official website of the Indonesia Stock Exchange or through the official websites of related companies. The data analysis used in this study was multiple linear regression analysis, with data processing tools, namely the Statistical Product and Service Solution (SPSS) version 25 application. The results of this study state that Corporate Social Responsibility has a significant negative effect on tax aggressiveness. However, Capital Intensity and Inventory Intensity do not significantly influence tax aggressiveness.